Tai Chi for Stroke Rehabilitation: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Lyu, Diyang; Lyu, Xuanxin; Zhang, Yong; Ren, Yi; Yang, Fan; Zhou, Li; Zou, Yihuai; Li, Zongheng (Frontiers in Physiology, 2018)
Background: Stroke is a major cause of poor health and has numerous complications. Tai Chi (TC) may have positive effects on the rehabilitation of stroke survivors, but recent clinical findings have not been included in previously published reviews. Objectives: We conducted this systematic review and meta-analysis to determine the effectiveness of all types of TC vs. conventional rehabilitation therapy for all aspects of stroke survivors' rehabilitation that have been studied. Method: We searched seven electronic literature databases (three in English, four in Chinese) and one clinical registry platform using established strategies to identify randomized controlled trials performed up to October 2017. Screening, quality assessment, and data collection were performed by two researchers separately, using the same standard. The results were analyzed using RevMan 5.3.0. The quality of evidence was evaluated with GRADEpro. Results: A total of 21 studies with 1,293 stroke survivors met inclusion criteria; 14 were included in the quantitative synthesis to evaluate four aspects and five outcomes. Nine studies indicated that TC was able to improve independent activities of daily living (ADL), especially TC vs. conventional rehabilitation therapy [mean difference (MD) [95% confidence interval (CI)] = 9.92 [6.82, 13.02], P < 0.00001]. Five studies reported significant effects of TC plus conventional rehabilitation therapy in increasing scores on the Fugl–Meyer Assessment for the upper limb [MD (95%CI) = 8.27 [4.69, 11.84], P < 0.0001], lower limb [MD (95%CI) = 2.75 [0.95, 4.56], P = 0.003], and overall [MD (95%CI) = 4.49 [1.92, 7.06], P = 0.0006]. The Berg Balance Scale revealed significant improvements according to pooled estimates for TC vs. conventional rehabilitation therapy [MD (95%CI) = 5.23 [3.42, 7.05], P < 0.00001]. TC plus conventional rehabilitation therapy also improved walking ability as measured by the Holden scale [MD (95%CI) = 0.61 [0.38, 0.85], P < 0.00001] and up-and-go time [MD (95%CI) = 2.59 [1.76, 3.43], P < 0.00001]. Conclusion: TC has an overall beneficial effect on ADL, balance, limb motor function, and walking ability among stroke survivors, based on very low-quality evidence, and may also improve sleep quality, mood, mental health, and other motor function. Well-designed, higher-quality trials with longer-term follow-up periods are needed to develop better-quality evidence.